2020
DOI: 10.2147/idr.s250878
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of Time to Sputum Culture Conversion Among Drug-Resistant Tuberculosis Patients in Oromia Region Hospitals, Ethiopia</p>

Abstract: Purpose: Multi-drug-resistant tuberculosis occurs when the tuberculosis bacteria develop resistance to at least the two most effective first-line anti-tuberculosis drugs, isoniazid and rifampicin. Sputum culture conversion is one of the indicators to monitor patients' prognosis throughout the treatment. Hence, this study aimed to assess time to culture conversion and its determinants among drug-resistant tuberculosis patients. Patients and Methods: A total of 228 drug-resistant tuberculosis patients in selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 30 publications
9
15
2
Order By: Relevance
“…This study revealed a median sputum smear conversion time of 35 days, IQR: 33 -68 days. This was in line with former studies that reported a median time of 35 days [28] and 34 days with an IQR of 28 -54 [23]. Alternatively, this finding was lower compared to a study finding from Afghanistan [20] where the sputum smear conversion time was 60 days.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study revealed a median sputum smear conversion time of 35 days, IQR: 33 -68 days. This was in line with former studies that reported a median time of 35 days [28] and 34 days with an IQR of 28 -54 [23]. Alternatively, this finding was lower compared to a study finding from Afghanistan [20] where the sputum smear conversion time was 60 days.…”
Section: Discussionsupporting
confidence: 91%
“…In most studies, the proportion of sputum smear conversion at the end of the 5 th treatment was consistent with our findings [22,23,28]. The proportions of smear conversion at the end of the 2 nd month of treatment on the other hand showed discrepancies with the former studies.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations